The temporal brightening of Uranus’ northern polar hood from HST/WFC3 and HST/STIs observations - James, A; Irwin, PGJ; Dobinson, J; Wong, MH; Tsubota, TK; Simon, AA; Fletcher, LN; Roman, MT; Teanby, NA; Toledo, D; Orton, GS (Wiley, 2023)
Hubble Space Telescope Wide-Field Camera 3 (HST/WFC3) observations spanning 2015 to 2021 confirm a brightening of Uranus' north polar hood feature with time. The vertical aerosol model of Irwin et al. (2023, https://doi.org/10.1038/s41550-023-02047-0) (IRW23), consisting of a deep haze layer based at ∼5 bar, a 1–2 bar haze layer, and an extended haze rising up from the 1–2 bar layer, was applied to retrievals on HST Space Telescope Imaging Spectrograph (STIS) (HST/STIS) observations (Sromovsky et al., 2014, 2019, https://doi.org/10.1016/j.icarus.2014.05.016, https://doi.org/10.1016/j.icarus.2018.06.026) revealing a reduction in cloud-top CH4 volume mixing ratio (VMR) (i.e., above the deep ∼5 bar haze) by an average of 0.0019 ± 0.0003 between 40–80◦N (∼10% average reduction) from 2012 to 2015. A combination of latitudinal retrievals on the HST/WFC3 and HST/STIS data sets, again employing the IRW23 model, reveal a temporal thickening of the 1–2 bar haze layer to be the main cause of the polar hood brightening, finding an average increase in integrated opacity of 1.09 ± 0.08 (∼33% increase) at 0.8 µm north of ∼45°N, concurrent with a decrease in the imaginary refractive index spectrum of the 1–2 bar haze layer north of ∼40°N and longwards of ∼0.7 µm. Small contributions to the brightening were found from a thickening of the deep aerosol layer, with an average increase in integrated opacity of 0.6 ± 0.1 (58% increase) north of 45°N between 2012 and 2015, and from the aforementioned decrease in CH4 VMR. Our results are consistent with the slowing of a stratospheric meridional circulation, exhibiting subsidence at the poles.